2011
DOI: 10.1002/kin.20555
|View full text |Cite
|
Sign up to set email alerts
|

Development of kinetic models for acid‐catalyzed methyl acetate formation reaction: Effect of catalyst concentration and water inhibition

Abstract: The reaction kinetics of reversible liquid-phase esterification of acetic acid with methanol is investigated in the temperature range 26-50 • C using sulfuric acid catalyst. The main goal of this work is to study the effect of catalyst concentration and sensitivity to the presence of water on the rate expression of this industrially important reaction. Experiments are conducted in an isothermal batch reactor and a second-order kinetic model is used to correlate the experimental data, which are found to fit wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
2
4
0
14
Order By: Relevance
“…However, as the reaction temperature increases, the rate of esterification reaction becomes faster. The present findings are in agreement with Ganesh et al , who also reported an increase in the rate of conversion of acetic acid with an increase in temperature.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…However, as the reaction temperature increases, the rate of esterification reaction becomes faster. The present findings are in agreement with Ganesh et al , who also reported an increase in the rate of conversion of acetic acid with an increase in temperature.…”
Section: Resultssupporting
confidence: 94%
“…From Eqn , it is possible to determine the K e values at different temperatures. The literature reported that the equilibrium constant ( K e ) values, based on concentration model, are in the range of 3.9–9.0 for the esterification of acetic acid with methanol reaction, as given in Ganesh et al , Jagadeesh babu et al and Tsai et al From the experiments, we obtained K e as 4.95.…”
Section: The Kinetic Modelsupporting
confidence: 52%
See 1 more Smart Citation
“…They concluded that heterogeneous catalysts gave poor conversions due to the diffusion problem of fatty acid into the pores of the catalyst. Henceforth, a lot of reports suggested that the homogeneous catalyst induces more conversion compared to heterogeneous catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The objective for implementation of these options is to achieve maximum conversion with high methyl acetate purity. The equilibrium constant for this reaction is about 5.0 [28] and it is independent of the temperature. The equilibrium conversion of the reaction is 69 %, when equimolar (1:1) quantities of reactants are used (base case), and the product purity corresponds to a methyl acetate weight fraction of only 0.55.…”
Section: Methyl Acetate Production Case Studymentioning
confidence: 96%